Pengaruh Promosi, dan Kepercayaan Merk Terhadap Loyalitas Merk pada Produk Fashion Aerostreet - Audy Susanto, Dimas; Arqy Ahmadi, Mirzam (PENG: Jurnal Ekonomi dan Manajemen, 2025)
Aerostreet, a local brand in the Indonesian fashion industry, faces challenges in building brand loyalty amidst fierce competition. Promotions attract consumers but do not necessarily result in long-term loyalty, while brand trust plays a key role in driving repeat purchases. This studi aims to provide insight into the factors that contribute to increasing consumer loyalty to the branding. The main focus of this study is to analyze the impact of promotion & brand trust on brand loyalty to AeroStreet fashion products. A quantitative approach was used with a survey method through an online questionnaire, involving > 30 respondents, both consumers and potential consumers of AeroStreet. Data were analyzed usiing Partial Least Squares Structural Equation Modeling (PLS-SEM ) to test the validity, reliability, and relationships between variables. The results showed that promotion did not have a significant effect on brand loyalty, while brand trust proved to be an important factor influencing loyalty. High consumer trust in the quality and reputation of the brand strengthens their loyalty. This study is the expected to be a reference for the academics & practitioners in understanding consumer behavior and formulating more effective marketing strategies for local fashion brands. Thus, improving these factors is expected to help local brands become more competitive and maintain consumer loyalty sustainably.